Ceramic Capillary Suspensions: Novel Processing Route for Macroporous Ceramic Materials. Issue 2 (24th December 2012) - Dittmann, Jens; Koos, Erin; Willenbacher, Norbert; Krell, A.
<x xml:space="preserve">Abstract</x> We introduce a novel method to produce macroporous ceramics by capillary suspensions. Adding a small amount (~1 vol%) of an immiscible secondary phase to a low concentration (~20 vol%) suspension can increase the yield stress by several orders of magnitude. This drastic change in flow behavior is induced by the creation of a sample‐spanning particle network in the suspension controlled by capillary forces. This strong network may persist even if the primary bulk phase is removed. Accordingly, capillary suspensions can be used as a precursor for manufacturing porous materials. Here, we focus on the specific features of this universal, low‐cost processing route for porous ceramics. An Al2O3 model system is used to demonstrate how to adjust porosity and pore size. With this system, we were able to achieve open porosities higher than 60% with an average pore size below 10 μm.